2015
DOI: 10.1177/0003319715576672
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is closely related to insulin resistance and the metabolic syndrome and might be an important cardiovascular (CV) risk factor. Epicardial adipose tissue (EAT) has been implicated in the pathogenesis of obesityrelated CV disease. In an NAFLD population, we investigated EAT thickness and its possible relations to NAFLD and cardiac structure and function. This was an observational study of 57 patients with NAFLD and 48 age-matched controls. Patients with NAFLD had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…We also showed an independent association between EAT, NASH and significant liver fibrosis, confirming recent results [ 30 , 49 ]. Interestingly, in these patients we observed a significant independent association between EAT and atherosclerosis and between EAT and liver damage, supporting the hypothesis that the cytokines/adipocytokines secreted by epicardial adipose tissue, acting as a paracrine tissue, favor the local inflammation in vessel and liver, being responsible for the damage of these districts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also showed an independent association between EAT, NASH and significant liver fibrosis, confirming recent results [ 30 , 49 ]. Interestingly, in these patients we observed a significant independent association between EAT and atherosclerosis and between EAT and liver damage, supporting the hypothesis that the cytokines/adipocytokines secreted by epicardial adipose tissue, acting as a paracrine tissue, favor the local inflammation in vessel and liver, being responsible for the damage of these districts.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we analyzed in a large series of subjects with NAFLD whether EAT correlates with cardiovascular and liver damage and we demonstrated that EAT is associated both with subclinical atherosclerosis and NASH and significant fibrosis independently of other metabolic confounders (BMI, waist circumference, diabetes, hypertension....) and that there is a significant relationship between increased value of EAT and cardiovascular and liver damage and metabolic alterations. The relationships between EAT, and cardiovascular damage has been recently reported in selected patients series[ 16 , 27 30 , 49 52 ], however this is the first study, to our knowledge, performed in a large series of well characterized NAFLD patients in whom we demonstrated a significant correlation between EAT values and atherosclerosis as documented by the independent association with cplaques. Previous observations suggested an association between epicardial adiposity and the presence and severity of coronary artery disease[ 17 19 , 24 , 53 ], and more recently with vascular stiffness, another subclinical sign of carotid atherosclerosis [ 29 , 54 ].…”
Section: Discussionmentioning
confidence: 53%
“…EAT deposition can be associated with coronary vascular disease pathogenesis mainly by the dysregulation of cardiac metabolic processes and the disruption of the epicardial and myocardial structural integrity. Other mechanisms that could be involved in the interaction between EAT and coronary vasculature are nerve damage and impaired cryoprotection of the heart[ 35 , 36 ]. Furthermore, the epicardial adipocytes exhibit and arrhythmogenic potential, a theory suggested by many clinical trials exploring the causative relationship between EAT and atrial fibrillation[ 21 ] (Figure 1 ).…”
Section: Epicardial Fat Type 2 Diabetes Mellitus and Coronary Arterymentioning
confidence: 99%
“… 7 9 Adiponectin is an adipokine secreted from EAT that has anti-inflammatory, antiatherogenic, and antihypertrophic via multiple cell-signaling mechanisms. 10 Adiponectin levels are reduced in different pathologic conditions, including metabolic syndrome, nonalcoholic fatty liver disease, diabetes, obesity, and ischemic heart disease 11 , 12 and have been also suggested as an independent prognostic biomarker in AF. 13 …”
Section: Introductionmentioning
confidence: 99%